Experimental study on the dynamic shear modulus and damping ratio of structural soft soils from the Yangtze River floodplain considering consolidation degree - Wang, Zhijun; Lv, Na; Xiao, Xing; Wu, Qi (Frontiers in Marine Science, 2025)
To explore the characteristics of the dynamic shear modulus of structural soft soil, undisturbed structural soft from the floodplain of the Yangtze River in Nanjing was subjected to strain-controlled cyclic triaxial tests to investigate how the initial effective confining pressure (σ'm), consolidation ratio (kc), and degree of consolidation (U) influence the maximum dynamic shear modulus Gmax and dynamic shear modulus (G) and damping ratio (λ). The results show that for this soil, G decreases with increasing shear strain amplitude (γ), and for a given γ, G increases with increasing σ'm, kc, and U. Compared with soil from the Yangtze estuary, kc has a greater effect on Gmax of the floodplain structural soft soil. Finally, a modified Martin-Davidenkov model is proposed for predicting G/Gmax of floodplain structural soft soil under different σ'm, kc, and U.